2021
DOI: 10.1111/ppc.13020
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the sexual care attitudes, beliefs and self‐efficacy of nursing students and gender roles: A cross‐sectional study

Abstract: Purpose: The aim of the research is to determine the relationship between the gender role approaches and the sexual care attitudes, beliefs, and self-efficacy of nursing students.Design and methods: This cross-sectional study included 109 nursing students.Findings: A negative correlation was found between the Gender Roles Attitude Scale and the Sexual Attitudes and Beliefs Scale (p < 0.001). A positive correlation was found between the Gender Roles Attitude Scale and the self-efficacy in clinical performance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Fuentes‐Pumarola et al ( 2021 ) found in their cross‐sectional descriptive study an association between sexual violence (rape and sexual assault being one of its forms) and alcohol consumption, either due to not being sufficiently aware due to its influence or because of the acceptance of these practices by ceasing in efforts to express rejection. Regarding sexual double standards, sporadic and frequent alcohol consumption increases adherence to the sexual double standard, which other authors find and associate with gender roles (Duman & Zengin Aydin, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Fuentes‐Pumarola et al ( 2021 ) found in their cross‐sectional descriptive study an association between sexual violence (rape and sexual assault being one of its forms) and alcohol consumption, either due to not being sufficiently aware due to its influence or because of the acceptance of these practices by ceasing in efforts to express rejection. Regarding sexual double standards, sporadic and frequent alcohol consumption increases adherence to the sexual double standard, which other authors find and associate with gender roles (Duman & Zengin Aydin, 2021 ).…”
Section: Discussionmentioning
confidence: 93%